Preparation method of aqueous zinc-sulfur battery positive electrode and aqueous zinc-sulfur battery thereof

CN122511809APending Publication Date: 2026-08-04HUBEI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610469557.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-04-10
Publication Date
2026-08-04

AI Technical Summary

Technical Problem

首先,碘催化剂的分散于电解液中导致催化位点与硫活性物质接触不充分,催化效率受限

Benefits of technology

[0025] The present invention also provides an aqueous zinc-sulfur battery, comprising a positive electrode, a negative electrode, a separator located between the positive electrode and the negative electrode, and an electrolyte, wherein the positive electrode is prepared by any of the above-described methods for preparing an aqueous zinc-sulfur battery positive electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122511809A_ABST
    Figure CN122511809A_ABST
Patent Text Reader

Abstract

This invention relates to a method for preparing a cathode for an aqueous zinc-sulfur battery and the corresponding aqueous zinc-sulfur battery. Addressing the problems of low catalytic efficiency and severe polyiodide shuttle effect caused by the addition of iodine catalyst to the electrolyte in traditional aqueous zinc-sulfur batteries, this invention loads trace amounts of iodine or iodides into the porous structure of an activated carbon support via physical adsorption, forming an iodine / activated carbon composite catalytic material, which is then combined with sulfur active materials to form a sulfur cathode. This design transfers the catalytic source from the electrolyte to the interior of the cathode, achieving zero-distance contact between the catalyst and the sulfur active materials, significantly improving the kinetics of the sulfur redox reaction and catalyst utilization. Simultaneously, the strong adsorption of iodine species by the activated carbon support effectively inhibits the dissolution and shuttle effect of polyiodides, preventing zinc anode corrosion and catalyst loss. The aqueous zinc-sulfur battery assembled with this cathode exhibits high reversible capacity, excellent rate performance, and long-term cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of aqueous zinc-ion battery technology, specifically to a method for preparing an aqueous zinc-sulfur battery cathode and an aqueous zinc-sulfur battery thereof. Background Technology

[0002] Aqueous zinc-sulfur batteries are known for their high theoretical capacity (1675 mAh g). -1 With its abundant resources, excellent safety, and environmental friendliness, sulfur cathode is considered a next-generation energy storage technology with great development potential. However, the inherent problems of sulfur cathode, such as slow redox kinetics, low utilization rate of active materials, and poor cycle stability, severely restrict its commercial application.

[0003] To improve the electrochemical performance of sulfur cathodes, known technical solutions in the art mainly involve adding iodine or iodide ions to the electrolyte as redox mediators to catalyze the sulfur conversion reaction. For example, in the prior art, I₂, ZnI₂, or other iodides are typically dissolved in an aqueous electrolyte, utilizing I₂... - / I3 - The redox couple accelerates the solid-liquid-solid multiphase reaction process, lowers the activation energy, and thus improves the rate performance and reversible capacity of the sulfur cathode. For example, CN121260951A discloses an electrolyte for improving the cycle stability of zinc-sulfur batteries. This electrolyte is prepared by mixing GaI3 additive, zinc sulfate, and a solvent. By adding iodide as an additive, the synergistic effect of anions and cations stabilizes the zinc anode and improves the reversible cycle performance of the sulfur cathode. Although this method improves reaction kinetics to some extent, it still has the following technical drawbacks: First, the dispersion of iodine catalyst in the electrolyte results in insufficient contact between the catalytic sites and the sulfur-active substances, thus limiting catalytic efficiency. Since catalytic reactions require effective contact at the solid-liquid interface, iodine ions far from the sulfur particle surface cannot fully exert their catalytic effect, leading to low catalyst utilization and a large required dosage.

[0004] Secondly, the polyiodide shuttle effect is severe. During charging and discharging, I3 is formed in the electrolyte. - I5 - Polyiodide ions can migrate to the negative electrode under the influence of an electric field, where they undergo side reactions with zinc metal, leading to continuous depletion of the iodine catalyst, corrosion of the zinc negative electrode, and a decrease in coulombic efficiency. This problem not only shortens the battery cycle life but also increases electrolyte maintenance costs.

[0005] In addition, adding iodine directly to the electrolyte increases the complexity and cost of the system, and poses additional challenges to the pH stability, ionic conductivity and compatibility with the membrane material of the electrolyte.

[0006] Therefore, developing a novel sulfur cathode structure that can effectively immobilize iodine catalysts, improve catalytic efficiency, and suppress polyiodide shuttle is of great significance for realizing the practical application of high-performance aqueous zinc-sulfur batteries. Summary of the Invention

[0007] The purpose of this invention is to overcome the shortcomings of existing technologies by providing a method for preparing an aqueous zinc-sulfur battery cathode and an aqueous zinc-sulfur battery. This invention introduces iodine as a catalyst source into the cathode to improve the solid-liquid-solid conversion rate of S→ZnS. The assembled aqueous zinc-sulfur battery operates at 0.2 A g... -1 It can provide 1500 mAh g -1 Its high capacity allows for the assembly of pouch cells with a capacity of 1 Ag. -1 Capacity reaches 800 mAh g at current -1 Stable cycle of 40 revolutions at 5 A g -1 It exhibits stable cycling performance of 450 cycles at a given current density. Simultaneously, it inhibits the dissolution of polyiodides generated during the reaction from the positive electrode into the electrolyte, thereby suppressing corrosion of the zinc negative electrode.

[0008] The technical solution provided by this invention is as follows: A method for preparing a positive electrode for an aqueous zinc-sulfur battery, comprising the following steps: 1) Under an inert atmosphere, Ketjen black and sulfur powder were dispersed in ethanol and stirred for 3 hours. After drying, the mixture was heated to carry out the reaction. After the reaction was completed, the mixture was cooled to obtain the KB@S composite material. 2) Mix the KB@S composite material, activated carbon, binder, and solvent, and stir to form a slurry; 3) The slurry is coated onto the current collector and dried to obtain the positive electrode precursor; 4) The positive electrode precursor and iodine are placed in a sealed container and heated. The positive electrode precursor absorbs iodine through sublimation adsorption to obtain the positive electrode of the aqueous zinc-sulfur battery.

[0009] By loading iodine catalyst in situ inside the positive electrode, zero-distance contact between the catalytic site and sulfur active material is achieved, significantly improving the redox reaction kinetics of sulfur and catalyst utilization. At the same time, the strong adsorption of iodine species by activated carbon effectively inhibits the dissolution of polyiodides and the shuttle effect, avoiding zinc anode corrosion, catalyst loss and side reactions. This greatly improves the reversible capacity, rate performance and long-cycle stability of aqueous zinc-sulfur batteries, providing a reliable process route for the high performance and practical application of batteries.

[0010] Preferably, in step 1), the drying temperature is 50~70 ℃, the reaction temperature is 150~180 ℃, and the reaction time is 10~14 hours.

[0011] Under mild conditions, sulfur and Ketjen black are fully melted, composited, and uniformly dispersed, ensuring that sulfur enters the pore structure of Ketjen black to form a stable conductive composite system. This avoids sulfur loss due to sublimation at excessively high temperatures or insufficient composite formation at excessively low temperatures. At the same time, it ensures the integrity of the composite material structure and its excellent conductivity, laying the material foundation for subsequent efficient catalysis and stable cycling, and improving the utilization rate of active materials and the stability of the electrode structure.

[0012] Preferably, in step 1), the mass ratio of Ketjen black to sulfur powder is 1:0.95-1.15.

[0013] By rationally balancing the construction of the conductive network and the loading of active materials, the high efficiency of sulfur loading and full utilization can be achieved while ensuring efficient electron transport channels. This avoids the decrease in conductivity and slow reaction kinetics caused by excessive sulfur, or the insufficient proportion of active materials and low capacity caused by excessive Ketjen black, so that the electrode achieves the optimal match between high capacity and high rate.

[0014] Preferably, in step 2), the mass ratio of KB@S composite material, activated carbon, and binder is 70-90:2-10:8-12.

[0015] To ensure the electrode has excellent formability, mechanical stability and conductivity, while keeping the activated carbon content within the optimal range, it can fully adsorb and fix the iodine catalyst and inhibit polyiodide shuttle, without reducing the proportion of active material due to excessive activated carbon; the appropriate amount of binder can ensure that the electrode structure is firm and not easy to pulverize and fall off, thereby improving the overall cycle life of the battery.

[0016] Preferably, in step 2), the solvent is N-methylpyrrolidone, the binder is polyvinylidene fluoride, and the solid content in the slurry is 0.20~0.28 g / mL. -1 .

[0017] The components are fully dissolved and uniformly dispersed in the solvent to obtain an electrode slurry with excellent flowability, coatability and stability, avoiding agglomeration, sedimentation or uneven coating. The appropriate solid content can ensure uniform electrode thickness and dense structure, improve electrode consistency and interface stability, and thus improve the reliability and repeatability of battery electrochemical performance.

[0018] Preferably, in step 3), the surface loading of sulfur powder in the slurry for the current collector is 1.5~2.0 mg / cm³. -2 The drying temperature is 55~65℃.

[0019] Achieving an optimal balance between high active material loading and rapid reaction kinetics ensures that the electrode possesses high mass and volumetric capacity to meet high energy density requirements, while also ensuring sufficient electrolyte penetration and rapid ion transport, avoiding problems such as increased polarization, incomplete reaction, and shortened cycle life caused by excessive areal loading. Thorough removal of residual solvents from the electrode under mild and dry conditions prevents solvent residues from causing charge-discharge side reactions and reducing coulombic efficiency; simultaneously, it prevents electrode structural deformation, uneven distribution of active materials, or binder failure due to excessive temperature, maintaining electrode interface stability and structural integrity, and improving battery cycle stability and safety.

[0020] Preferably, in step 4), the amount of iodine used is 0.2 to 2 times the amount of activated carbon used (by mass).

[0021] While ensuring the efficient catalytic effect of iodine on sulfur redox reaction, it avoids excessive dissolution of polyiodides and shuttle effect caused by excessive iodine, and reduces catalyst loss and zinc anode corrosion. Trace amounts of iodine can significantly improve reaction kinetics, reduce catalyst cost, and achieve a synergistic improvement in high catalytic efficiency, low shuttle effect and long cycle life.

[0022] Preferably, in step 4), the heating temperature is 60~160 ℃ and the heating time is 10~14 hours.

[0023] This allows elemental iodine to fully sublimate and uniformly adsorb into the pore structure of activated carbon, achieving uniform loading and efficient anchoring of iodine inside the cathode, ensuring uniform distribution of catalytic sites and maximizing utilization. Suitable temperature and time can avoid insufficient iodine adsorption or excessive aggregation, ensuring stable catalytic effect and long-lasting inhibition of polyiodide shuttle.

[0024] The present invention also provides an application of the aqueous zinc-sulfur battery cathode obtained by the above preparation method in the preparation of aqueous zinc-sulfur batteries.

[0025] The present invention also provides an aqueous zinc-sulfur battery, comprising a positive electrode, a negative electrode, a separator located between the positive electrode and the negative electrode, and an electrolyte, wherein the positive electrode is prepared by any of the above-described methods for preparing an aqueous zinc-sulfur battery positive electrode.

[0026] The beneficial effects of this invention are as follows: By loading iodine into activated carbon in the cathode, this invention constructs a supported iodine-catalyzed sulfur cathode, significantly improving the performance of aqueous zinc-sulfur batteries in terms of catalytic efficiency, structural stability, and electrochemical performance. This design places the iodine catalyst source inside the cathode, achieving zero-distance contact with the sulfur active material, greatly improving sulfur oxidation-reduction kinetics and catalyst utilization, reducing reaction polarization, and increasing the conversion depth of the active material. The activated carbon support can strongly adsorb and fix iodine species, effectively inhibiting the dissolution of polyiodides and the shuttle effect, avoiding zinc anode corrosion, byproduct accumulation, and catalyst loss, significantly improving the overall stability of the electrode and the battery. Attached Figure Description

[0027] To more clearly illustrate the technical solutions of the embodiments disclosed in this invention, the accompanying drawings of the embodiments will be briefly described below. These drawings are for illustrative purposes only and are not intended to limit the scope of protection of this invention.

[0028] Figure 1 The charge-discharge curves of the positive electrode of the aqueous zinc-sulfur battery under different iodine loadings in Examples 1-3 are shown. Figure 2 The charge-discharge curves of the positive electrode of the aqueous zinc-sulfur battery under different iodine loading temperatures in Examples 1, 4, and 5 are shown. Figure 3 The images show the dissolution of polyiodide in the electrolyte during the charging and discharging process of the electrodes prepared in Example 1 and Comparative Example 1, and the corrosion of the zinc anode after charge-discharge cycles. Figure 4 SEM images of the zinc anodes corresponding to the KSAI-1 and KS positive electrodes after charge-discharge cycles were prepared for Example 1 and Comparative Example 1. Figure 5 The XRD patterns of the zinc anodes corresponding to the KSAI-1 and KS positive electrodes prepared in Example 1 and Comparative Example 1 after charge-discharge cycles are shown. Figure 6 The UV and Raman spectra of the electrolytes corresponding to KSAI-1 and KS cathodes prepared in Example 1 and Comparative Example 1 after charge-discharge cycles are shown. Figure 7 Semi-in-situ XRD comparison images of KSAI-1 and KS cathodes prepared in Example 1 and Comparative Example 1 at different charge and discharge potentials; Figure 8 The rate performance comparison charts for KSAI-1 and KS cathodes prepared in Example 1 and Comparative Example 1 are shown; where a is the charge-discharge curve of KSAI-1 cathode prepared in Example 1 at different current densities; b is the comparison chart of the specific capacity and coulombic efficiency changes of KSAI-1 and KS cathodes prepared in Example 1 and Comparative Example 1 at different cycle numbers. Figure 9 KSAI-1 and KS cathodes were prepared for Example 1 and Comparative Example 1 at 5 A g.-1 Comparison of specific capacity and coulombic efficiency under long-cycle conditions; Figure 10 The soft-pack aqueous zinc-sulfur battery assembled with the KSAI-1 cathode prepared in Example 1 was tested at 1 A g. -1 Cyclic performance curves at current density. Detailed Implementation

[0029] The technical solutions (including preferred technical solutions) of the present invention will be further described in detail below with reference to the accompanying drawings and by way of listing some optional embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0030] Example 1 This embodiment provides a method for preparing an aqueous zinc-sulfur battery cathode (denoted as KSAI-1) and the method thereof, including the following steps: 1) Under an argon atmosphere, 40 mg of sulfur powder and 40 mg of Ketjen black were uniformly dispersed in ethanol and stirred for 3 hours. The mixture was then dried at 60 °C and reacted at 160 °C for 12 hours. After cooling to room temperature, the KB@S composite material was obtained.

[0031] 2) Weigh 80 mg of KB@S composite material, 5 mg of activated carbon, 10 mg of polyvinylidene fluoride (PVDF, binder), and 400 μL of N-methylpyrrolidone (NMP), and stir to form a slurry.

[0032] 3) Coat the prepared slurry onto carbon cloth, controlling the surface loading of the active material (S) to be 1.5~2.0 mg / cm³. -2 The cathode precursor was obtained by placing it in a vacuum environment and drying it at 60 °C for 10 hours.

[0033] 4) The positive electrode precursor is sized to 0.785 cm. 2 The area is cut into a circular piece, 5 mg of iodine is placed in a plastic tube, sealed and placed in a 60 ℃ oven for 12 hours to fully absorb the iodine, thus obtaining the positive electrode of an aqueous zinc-sulfur battery.

[0034] Example 2 This embodiment provides a method for preparing an aqueous zinc-sulfur battery cathode (denoted as KSAI-2), and the preparation method is basically the same as that in Example 1, except that in step 4), the amount of iodine used is 1 mg.

[0035] Example 3 This embodiment provides a method for preparing an aqueous zinc-sulfur battery cathode (denoted as KSAI-3), and the preparation method is basically the same as that in Example 1, except that in step 4), the amount of iodine used is 10 mg.

[0036] Example 4 This embodiment provides a method for preparing an aqueous zinc-sulfur battery cathode (denoted as KSAI-4), which is basically the same as that in Example 1, except that in step 4), after sealing, it is placed in an oven at 120 ℃ for 12 hours to react.

[0037] Example 5 This embodiment provides a method for preparing an aqueous zinc-sulfur battery cathode (denoted as KSAI-5), which is basically the same as that in Example 1, except that in step 4), after sealing, it is placed in an oven at 160 ℃ for 12 hours to react.

[0038] Comparative Example 1 This comparative example provides a method for preparing an aqueous zinc-sulfur battery cathode (denoted as KS) and the method thereof, including the following steps: 1) Under an argon atmosphere, 40 mg of sulfur powder and 40 mg of Ketjen black were uniformly dispersed in ethanol, dried at 60 °C, and then reacted at 160 °C for 12 hours. After cooling to room temperature, the KB@S composite material was obtained.

[0039] 2) Weigh 80 mg of KB@S composite material, 10 mg of conductive carbon black, and 10 mg of polyvinylidene fluoride (PVDF, binder), and mix them with N-methylpyrrolidone (NMP) as the solvent to form a slurry.

[0040] 3) Coat the prepared slurry onto carbon cloth, controlling the surface loading of the active material to be 1.5~2.0 mg cm⁻¹. -2 After being placed in a vacuum environment and dried at 60 °C for 10 hours, it was then pressed into a 0.785 cm³ container. 2 Cut the area into a circular piece to obtain the positive electrode of the aqueous zinc-sulfur battery.

[0041] The positive electrode sheets prepared in the above examples and comparative examples were used to assemble CR2025 coin cells for cycle performance testing. The negative electrode used was a 10 mm diameter zinc foil, the positive electrode used was a 10 mm diameter sulfur positive electrode, the separator used was a 16 mm diameter glass fiber (GF), and the electrolyte used was 2 mol / L. -1 Zinc sulfate electrolyte. Assembled using a "sandwich" structure.

[0042] A pouch cell was assembled using a 3×3 cm zinc foil, a 3×3 cm sulfur cathode, and a 4×4 cm glass fiber separator. The electrolyte was also 2 mol / L.-1 Electrochemical performance tests were conducted on zinc sulfate electrolyte.

[0043] like Figure 1 As shown, at 0.2 Ag -1 At the specified current density, Example 1 showed the highest match between the iodine content and the pore adsorption capacity of activated carbon, as well as the reaction requirements of sulfur-containing active materials. This ensured sufficient catalytic sites while effectively immobilizing iodine species through the strong adsorption of activated carbon, preventing the dissolution of polyiodides and resulting in a high reversible capacity. When the iodine content decreased, Example 2 exhibited insufficient catalytic sites and inadequate contact with sulfur-containing active materials, failing to effectively accelerate the S→ZnS redox reaction. This led to an unstable charge / discharge voltage plateau at the sulfur cathode, low reversible capacity, and poor rate performance. Simultaneously, limited catalytic efficiency resulted in sluggish overall battery reaction kinetics. Example 3 showed that while an increased iodine content resulted in a higher initial capacity, plateau decay was likely to occur because excess iodine exceeded the activated carbon adsorption threshold, causing polyiodide dissolution and triggering side reactions.

[0044] like Figure 2 As shown, at 5 A g -1 At the specified current density, KSAI-5 loaded with iodine in Example 5 at 160 °C exhibited a higher initial capacity, but its capacity rapidly deteriorated after 250 cycles. In contrast, KSAI-1 loaded with iodine in Example 1 at 60 °C, while having a slightly lower initial capacity, achieved stable cycling for 800 cycles. This difference can be attributed to the spatial distribution and binding state of iodine in the activated carbon. High temperatures promote the diffusion of iodine vapor into the depths of the micropores, providing a high initial iodide ion concentration and thus increasing capacity. However, deeply embedded iodine leads to mechanical damage to the microporous structure during repeated redox processes, inducing polyiodide shuttle and catalyst deactivation. Conversely, at the lower temperature of 60 °C, iodine is mainly adsorbed on the mesopores and outer surface. Although the initial active site density is lower, pore structure destruction is avoided, ensuring structural integrity and confinement effect during long-term cycling.

[0045] like Figures 3-4 As shown, morphologically, the KS positive electrode provided in Comparative Example 1 exhibits significant dissolution in the electrolyte, and its corresponding negative electrode region shows a rough and uneven surface after cycling, with numerous corrosion pits, damage sites, and obvious impurity particles. Microstructurally, its zinc negative electrode surface is rough and uneven, showing obvious corrosion pits, loose deposits, and irregular protrusions, indicating severe side reactions and corrosion. The KSAI-1 positive electrode provided in Example 1 did not show significant dissolution in the electrolyte. Microstructurally, its corresponding zinc negative electrode surface is generally smooth and dense, without obvious pores, damage, or impurity adhesion, showing no significant microscopic damage.

[0046] From the XRD spectrum ( Figure 5As can be seen, after cyclic charge and discharge, the zinc anode corresponding to the KS positive electrode provided in Comparative Example 1 showed obvious impurities, an uneven baseline, and disordered peak intensities, with a distinct peak near 2θ=10°, indicating the formation of a large amount of corrosion byproducts. In contrast, the zinc anode corresponding to the KSAI-1 positive electrode provided in Example 1 only showed sharp, clean Zn diffraction peaks, without obvious impurities, with regular peak shapes and almost no corrosion product signals. This indicates that the KSAI-1 positive electrode provided in Example 1 effectively suppressed the dissolution and shuttle of polyiodides, and the zinc anode did not undergo significant side reactions with polyiodides, thus well protecting the structural integrity of the anode.

[0047] Further analysis of the internal structure, such as Figure 6 As shown, after cyclic charging and discharging, the Raman signal of the electrolyte corresponding to the KS cathode provided in Comparative Example 1 is weak, and the ultraviolet spectrum shows strong polyiodide characteristic absorption, corresponding to the dissolution of a large amount of polyiodides; the Raman characteristic peak of the electrolyte corresponding to the KSAI-1 cathode provided in Example 1 is stronger and the structure is more stable, and the ultraviolet spectrum shows that almost no polyiodides are dissolved in the electrolyte.

[0048] like Figure 7 As shown, the KSAI-1 cathode provided in Example 1 exhibits a strong and sharp ZnS characteristic diffraction peak during the discharge stage, which completely disappears after charging, demonstrating excellent S↔ZnS reversible phase transition behavior. In contrast, the ZnS diffraction peak of the KS cathode provided in Comparative Example 1 is weak and has poor reversibility. This indicates that the preparation method using iodine-supported catalysis can significantly accelerate the redox kinetics of sulfur, improve the reversible utilization rate and conversion depth of sulfur, and provide key mechanistic support for achieving high capacity and long cycle life in aqueous zinc-sulfur batteries.

[0049] like Figure 8 As shown in a, in the range of 0.2~5 Ag -1 Within the current density range, the KSAI-1 cathode provided in Example 1 exhibited a specific capacity significantly higher than that of the KS cathode, and the capacity decayed gradually with increasing current density. Figure 8As shown in b, with increasing cycle count, the KSAI-1 cathode provided in Example 1 maintains a stable specific capacity with an extremely slow decay rate. Its initial specific capacity is high, and there are no significant fluctuations during cycling. Even after multiple cycles, it maintains a high specific capacity level without a significant decline, demonstrating excellent cycling stability. In contrast, the KS cathode provided in Comparative Example 1 exhibits rapid capacity decay and significant fluctuations. Its initial specific capacity is lower than that of Example 1, and it declines significantly after only a few cycles, with a substantial decrease in specific capacity in the later stages of cycling. This indicates that without iodine loading, the polyiodide shuttle effect is significant, leading to loss of active material and rapid capacity decay. Similarly, the coulombic efficiency of the KSAI-1 cathode provided in Example 1 remains consistently high with minimal fluctuations as the number of cycles increases. In contrast, the coulombic efficiency of the KS cathode provided in Comparative Example 1 is generally low and fluctuates significantly; it is difficult to maintain stable coulombic efficiency during cycling. Furthermore, the KS cathode provided in Comparative Example 1 has a low capacity that decreases sharply under high current.

[0050] like Figure 9 As shown, the number of cycles is extended to 5 A g -1 At the specified current density, the KSAI-1 cathode provided in Example 1 exhibited excellent long-term cycling stability, maintaining high reversible capacity after 450 cycles, with a coulombic efficiency consistently close to 100%. In contrast, the KS cathode provided in Comparative Example 1 showed rapid capacity decay and extremely poor cycling stability. This demonstrates that the iodine-supported catalytic preparation method can significantly accelerate the redox kinetics of sulfur, improve the utilization rate of active materials and rate performance, enabling the battery to maintain high capacity output even under high-current charge and discharge conditions.

[0051] like Figure 10 As shown, a pouch cell was assembled using a 3×3 cm zinc foil, a 3×3 cm KSAI-1 positive electrode provided in Example 1, and a 4×4 cm glass fiber separator. The electrolyte was also 2 mol L⁻¹. -1 Electrochemical performance tests were conducted using zinc sulfate electrolyte. The initial capacity of its soft-pack aqueous zinc-sulfur battery reached 800 mAh g⁻¹. -1 After 40 cycles, the capacity showed no significant decay, and the coulombic efficiency remained stable at nearly 100%, demonstrating excellent cycle stability and reversibility.

[0052] It will be readily understood by those skilled in the art that the above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, combinations, substitutions, improvements, etc., made under the spirit and principles of the present invention are included within the protection scope of the present invention.

Claims

1. A method for preparing a positive electrode for an aqueous zinc-sulfur battery, characterized in that, Includes the following steps: 1) Under an inert atmosphere, Ketjen black and sulfur powder were dispersed in ethanol, dried, and then heated to react. After the reaction was completed, the mixture was cooled to obtain the KB@S composite material. 2) Mix the KB@S composite material, activated carbon, binder, and solvent, and stir to form a slurry; 3) The slurry is coated onto the current collector and dried to obtain the positive electrode precursor; 4) The positive electrode precursor and iodine are placed in a sealed container and heated to obtain the positive electrode of the aqueous zinc-sulfur battery.

2. The method for preparing an aqueous zinc-sulfur battery cathode according to claim 1, characterized in that, In step 1), the drying temperature is 50~70 ℃, the reaction temperature is 150~180 ℃, and the reaction time is 10~14 hours.

3. The method for preparing an aqueous zinc-sulfur battery cathode according to claim 1, characterized in that, In step 1), the mass ratio of Ketjen black to sulfur powder is 1:0.95-1.

15.

4. The method for preparing an aqueous zinc-sulfur battery cathode according to claim 1, characterized in that, In step 2), the mass ratio of KB@S composite material, activated carbon, and binder is 70-90:2-10:8-12.

5. The method for preparing an aqueous zinc-sulfur battery cathode according to claim 4, characterized in that, In step 2), the solvent is N-methylpyrrolidone, the binder is polyvinylidene fluoride, and the solid content in the slurry is 0.20~0.28 g / mL. -1 .

6. The method for preparing an aqueous zinc-sulfur battery cathode according to claim 1, characterized in that, In step 3), the surface loading of sulfur powder in the slurry for the current collector is 1.5~2.0 mg / cm³. -2 The drying temperature is 55~65℃.

7. The method for preparing an aqueous zinc-sulfur battery cathode according to claim 1, characterized in that, In step 4), based on the mass of activated carbon, the amount of iodine used is 0.2 to 2 times the mass of activated carbon.

8. The method for preparing an aqueous zinc-sulfur battery cathode according to claim 1, characterized in that, In step 4), the heating temperature is 60~160 ℃ and the heating time is 10~14 hours.

9. The application of an aqueous zinc-sulfur battery cathode obtained by the preparation method according to claim 1 in the preparation of aqueous zinc-sulfur batteries.

10. An aqueous zinc-sulfur battery, comprising a positive electrode, a negative electrode, a separator located between the positive electrode and the negative electrode, and an electrolyte, characterized in that, The positive electrode is an aqueous zinc-sulfur battery positive electrode prepared by any one of the methods described in claims 1-8.